Reliability of externally fixed dynamometry hamstring strength testing in elite youth football players - Wollin, M.; Purdam, C.; Drew, M. K. (Journal of Science and Medicine in Sport, 2016)
Objectives: To investigate inter and intra-tester reliability of an externally fixed dynamometry unilateral hamstring strength test, in the elite sports setting. Design: Reliability study. Methods: Sixteen, injury-free, elite male youth football players (age = 16.81 ± 0.54 years, height = 180.22 ± 5.29 cm, weight 73.88 ± 6.54 kg, BMI = 22.57 ± 1.42) gave written informed consent. Unilateral maximum isometric peak hamstring force was evaluated by externally fixed dynamometry for inter-tester, intra-day and intra-tester, inter-week reliability. The test position was standardised to correlate with the terminal swing phase of the gait running cycle. Results: Inter and intra-tester values demonstrated good to high levels of reliability. The intra-class coefficient (ICC) for inter-tester, intra-day reliability was 0.87 (95% CI = 0.75-0.93) with standard error of measure percentage (SEM%) 4.7 and minimal detectable change percentage (MDC%) 12.9. Intra-tester, inter-week reliability results were ICC 0.86 (95% CI, 0.74-0.93), SEM% 5.0 and MDC% 14.0. Conclusions: This study demonstrates good to high inter and intra-tester reliability of isometric externally fixed dynamometry unilateral hamstring strength testing in the regular elite sport setting involving elite male youth football players. The intra-class coefficient in association with the low standard error of measure and minimal detectable change percentages suggest that this procedure is appropriate for clinical and academic use as well as monitoring hamstring strength in the elite sport setting.